The effect of electronical film on the anxiety of patients candidate for lumbar disc surgery - Mohamadreza Abdi; Zahra Ghazavi; Saied Abrishamkar (Wolters Kluwer Medknow Publications, 2019)
Background: This study aimed at investigating the effect of showing surgery educational documentary film on the anxiety of patients candidate for lumbar disc surgery. Materials and Methods: This study, as a randomized clinical trial, was conducted in 2018 on 60 patients undergoing lumbar disc surgery, Iran. The patients were divided into two groups of intervention and control (N = 30). An educational film was shown to the patients of the intervention group for 20 min and the control group was provided with the ward's routine trainings. All patients completed demographic characteristics questionnaire and the Spielberger State-Trait Anxiety Inventory (SSTAI) on the admission day, 1 day before the surgery, and 2 h before the surgery. SSTAI was recompleted by the patients. Data analysis was performed using independent t-test, Chi-square, Mann-Whitney test, and paired t-test. Results: Before the intervention, the mean score of the state (obvious) and trait (hidden) anxieties was not significantly different between the two groups, but after the intervention, the mean [standard deviation (SD)] score of the state anxiety in the intervention group was significantly lower than that of the control group [mean (SD) = 40.78 (10.34) vs. 47.45 (10.33), F10,33= 58,p= 0.01]. In addition, after the intervention, the mean (SD) anxiety score of the patients in the intervention group was significantly lower than that of the control group [mean (SD) = 38.65 (11.01) vs. 44.71 (10.34), F10,34= 58, p= 0.03). Conclusions: The results showed that educational film reduces the patients' level of anxiety before the surgery. As such, it is recommended that these trainings be included in preoperative nursing practices.